Contributions of entrepreneurship to strategic success Entrepreneurial contributions of business organizations in achieving strategic success - Hasan Abdulsalam Ali Emran; Fathia .M. Elhony (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to investigate the contribution of leadership in achieving strategic success in business organizations. The study was motivated by the increasing importance of environmental variables and the need to understand the relationship between variables. The study focused on Tragan Teaching Hospital's administrative leaders, with a sample of 15 individuals selected through comprehensive inventory methods. The data was collected using a questionnaire and processed using various statistical methods. The study's hypothesis was to identify the relationship and impact between leadership and strategic success. The results indicated a statistically significant relationship between leadership and achieving strategic success. Overall, the study highlights the crucial role of leadership in attaining strategic success in business organizations